The Effect of Social Factors and Brand Image on The Decision of Parents in Choosing Education Services Educated by The Parent's Attitude - Khair, Muthi Abul; Maesaroh, Eka Siti; Aisjah, Siti; Sunaryo, Sunaryo (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
This study aims to examine and analyze the influence of social factors and brand image on decision making mediated by the attitude of parents of Al-Izzah Natural Elementary School, Sidoarjo Regency. The sampling technique is probability sampling and uses a saturated sampling method with a sample of 84 respondents. However, only 83 questionnaires can be processed using Partial Least Square. The results showed that social factors and brand image influence attitudes and decisions and attitudes also influence decisions. Looking at the mediating variables shows that attitudes give a partial mediating role to the influence of social factors and brand image on decisions. In further research, it is recommended to add new variables and the scope of the sample population to provide more complex and different results.